Photoresponsive amphiphilic azobenzene–PEG self-assembles to form supramolecular nanostructures for drug delivery applications. Issue 10 (20th January 2016) - Yadav, Santosh; Deka, Smriti Rekha; Verma, Geeta; Sharma, Ashwani Kumar; Kumar, Pradeep
Abstract : Self-assembled smart nanostructures have emerged as controlled and site-specific systems for drug delivery applications. Abstract : Self-assembled smart nanostructures have emerged as controlled and site-specific systems for drug delivery applications. An amphiphilic polymer series, Azo-PEG-NHBoc, Azo-PEG-NH2 and Azo-PEG-Gn, was formed by the reaction of 4-(4-isothiocyanatophenylazo)- N, N -dimethylaniline (ITPADA) with biocompatible functionalized polyethylene glycol which self-assembled in aqueous solutions to form nanostructures. Light-controlled reversible assembly and disassembly, and enzyme-mediated morphological changes in the nanostructures were investigated by DLS and TEM measurements. Entrapment of hydrophobic drugs in the core and their release under the influence of external stimuli such as light and enzyme demonstrated the potential of such nanostructures in drug delivery applications.